Liquid crystalline polymers IX Main chain thermotropic poly (azomethine – ether)s containing thiazole moiety linked with polymethylene spacers (eXPRESS Polymer Letters, 2007)
A new homologous series of thermally stable thermotropic liquid crystalline poly(azomethine-ether)s based on thiazole moiety were synthesized by solution polycondensation of 4,4`-diformyl-α,ω-diphenoxyalkanes, I–IV or 4,4`-diformyl-2,2`-dimethoxy-α,ω-diphenoxyalkanes V–VIII with the new bis(2-aminothiazole) monomer X. A model compound XI was synthesized from X with benzaldehyde and characterized by elemental and spectral analyses. The inherent viscosities of the resulting polymers were in the range 0.43–1.34 dI/g. All the poly(azomethine-ether)s were insoluble in common organic solvents but dissolved completely in concentrated H2SO4 and formic acid. The mesomorphic properties of these polymers were studied as a function of the diphenoxyalkane space length. Their thermotropic liquid crystalline properties were examined by DSC and optical polarizing microscopy and demonstrated that the resulting polymers form nematic mesophases over wide temperature ranges. The thermogravimetric analyses of those polymers were evaluated by TGA and DSC measurements and correlated to their structural units. X-ray analysis showed that polymers having some degree of crystallinity in the region 2θ = 5–60°. In addition, the morphological properties of selected examples were tested by scanning electron microscopy.